Isocitrate Dehydrogenase 1 and 2 Mutations in Pediatric Neuroblastoma Patients - Emre LEVENTOGLU; Gurses SAHIN; Sule YESIL; Ceyhun BOZKURT; Nazmiye YUKSEK; Ali FETTAH; Sule TOPRAK; Burcak KURUCU BILGIN; Emre CAPKINOGLU; Nilgun EROGLU; Sibel AKPINAR TEKGUNDUZ; Ayse Ulya ERTEM (Medeniyet Medical Journal)
Objective: Neuroblastoma is one of the common tumors of childhood. The demonstration of new factors such as isocitrate dehydrogenase 1 (IDH1) and isocitrate dehydrogenase 2 (IDH2) mutations will be important in the diagnosis and treatment. IDH1 and IDH2 mutations have been found in many types of cancer, such as malignant gliomas, acute myeloid leukemias, chondrosarcoma, and thyroid carcinoma. This study aimed to investigate the presence of IDH1 or IDH2 mutations in patients with neuroblastoma and to determine whether these mutations were different in terms of age, clinical findings, and response to treatment. Methods: Biopsy specimens of 25 patients with pediatric neuroblastoma patients were evaluated for IDH mutations. The clinical and laboratory features of the patients with/without mutation were retrospectively analyzed from a hospital database. Results: A total of 25 patients for whom genetic analysis could be performed were included in the study (60% male, n=15). The mean age was 32.2+-25.9 months (3 days-96 months). IDH1 mutation was detected in 8 (32%) and IDH2 mutations in 5 (20%) patients. These mutations showed no statistically significant relationship with age, tumor localization, laboratory results, stage, and prognosis. However, in the case of IDH mutation, patients were diagnosed at the advanced stage. Conclusions: This study demonstrated the relationship between neuroblastoma and IDH mutation for the first time. Because to the fact that the mutation is very heterogeneous, it would be appropriate to conduct a larger series of patients in terms of the impact of the clinical significance of each mutation on the diagnosis and prognosis.